Molecular Characterisation of Murray Valley Encephalitis Virus - Diviney, Sinead; Williams, David; Geerlings, K.; Chua, B.; Yu, M.; Hansson, E.; Wang, L.; MacKenzie, John (Unknown, 2007)
Murray Valley encephalitis viru's (MVEV) is an encephalitogenic mosquito-borne flavivirus endemic to Australia and Papua New Guinea (PNG). Four genotypes (GI-IV) of MVEV have been previously recognised: GI and GIl circulate in the Australian mainland, while GIll and GIV circulate in PNG. Prior to this study, only one full length genome of MVEV had been reported, that of the prototype strain MVE-I-51 (GI). Here, we report full length genomic sequences of strains representing each of the three other genotypes: OR 156 (GIl), NG 156 (GIll) and MK66S4 (GIV). Sequence information was derived using a combination of cDNA subtraction, RT-PCR and 5'- and 3'-RACE. Nucleotide (and amino acid) sequence analysis revealed high levels of similarity between strains, ranging from 90.6% (n.1 %) and 94.1 % (9S.S%); highest levels of identity were found in the non-structural NS5 gene. Phylogenctic analysis using complete envelope (E) gene sequence information was consistent with previous partial E gene analyses and the identification of four distinct genetic types of MVEV. However, analyses with full length genomic and pre-rnernbrane gene sequences revealed a much closer relationship between the PNG strains NG 156 and MK6684, and indicated their grouping as a single genotype.